2010
DOI: 10.1055/s-0029-1241867
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant without Intubation in Preterm Infants with Respiratory Distress: First Multi-center Data

Abstract: A new method of surfactant application was associated with a lower prevalence of mechanical ventilation and better pulmonary outcome. A prospective controlled trial is required to determine whether this approach is superior to standard care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 16 publications
5
82
2
4
Order By: Relevance
“…The proposed method consists in the combination of two efficient methods of RDS therapy: surfactant and nasal CPAP. The obtained results demonstrated decrease in BPD development and mortality rates, as well as in the rate of glucocorticoid use [8,9]. Analysis of clinical studies of surfactant drugs demonstrated that these drugs of animal origin are efficient for RDS prevention and treatment.…”
mentioning
confidence: 79%
“…The proposed method consists in the combination of two efficient methods of RDS therapy: surfactant and nasal CPAP. The obtained results demonstrated decrease in BPD development and mortality rates, as well as in the rate of glucocorticoid use [8,9]. Analysis of clinical studies of surfactant drugs demonstrated that these drugs of animal origin are efficient for RDS prevention and treatment.…”
mentioning
confidence: 79%
“…Результаты рандомизированных сравнительных иссле-дований у интубированных новорожденных, получавших сурфактант, и у детей, находящихся на респираторной под-держке через назальные канюли с позитивным давлением (Nasal Continuous Positive Airway Pressure, nСРАР), начатой в родзале, продемонстрировали преимущества последней в отношении необходимости интубации, глюкокортико-стероидной (ГКС) терапии, количества дней механиче-ской вентиляции. Различий в смертности и частоте БЛД к 36-й нед гестационного возраста в этих группах не обна-ружено [40,41]. В этой связи новорожденным 24-28 нед гестации рекомендована следующая последовательность мероприятий, позволяющая снизить частоту механической вентиляции легких: интубация сразу после рождения, вве-дение дозы сурфактанта, экстубация и СРАР [42].…”
Section: исходы бронхолегочной дисплазииunclassified
“…nose continious positive airway pressure, т. е. на дыхание через носовые канюли с постоянным положительным давле-нием в дыхательных путях), либо спонтанно дышащим очень незрелым детям (22-26 нед гестации) сразу после рождения проводят NСРАР, и с помощью тонкого эндо-трахеального катетера болюсно вводят сурфактант без интубации (surfactant without intubation, SWI). В резуль-тате удается добиться снижения частоты использования системных глюкокортикоидов, частоты формирования БЛД, летальности [6][7][8].…”
Section: Introductionunclassified